Internet of Things (IoT) impact on facility management of office buildings: A qualitative study - Jaya Devi, Anathan; Liyana, Mohamed Yusof; Rahimi, A. Rahman (Engineering Project and Production Management, 2023)
Most office buildings are not optimal due to the slow adoption of the Internet of Things (IoT) in facility management (FM) processes. As a result, the collected data, information, and system processing are not completely exploited. In consequence, the impacts of IoT on FM are expected to intensify soon. However, the integration of IoT and FM in implementing new technologies, capabilities for high-quality service delivery, and changes in management approaches in office buildings are still low. This study intends to explore IoT's positive and negative impacts on the FM of office buildings. The data was collected from open-ended interviews with 20 FM professionals and analyzed using the thematic analysis method to identify the impacts of IoT on FM office buildings. The findings show that IoT positively and negatively impacts the FM of office buildings in terms of people, system, safety, time, and cost. The study findings can assist key FM players in developing and creating a better convergence of people, place, environment, and process for business and services in office buildings by considering impacts.